2011
DOI: 10.1055/s-0031-1299848
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering Properties and Safety of Chitosan

Abstract: Chitosan (CAS 9012-76-4) is derived by alkaline deacetylation from chitin, an abundant polymeric product of natural biosynthesis especially in crustaceans. It is available in a primary, unorganised structure, but also in a microcrystalline form. As a dietary supplement, chitosan has been claimed to control obesity and to lower serum cholesterol. A variety of chitosan products have been freely available worldwide in health stores and pharmacies. This review summarises the current knowledge about cholesterol-low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 23 publications
1
66
1
2
Order By: Relevance
“…Gades and Stern reported that quantities exceeding 4.5 g chitosan taken daily by human volunteers did not result in toxic effects (Gades & Stern, 2003). In addition, human trials up to twelve weeks showed no toxic effects, no allergies, and only nausea symptoms and constipation in 2.6 -5.4% of subjects (Ylitalo et al, 2002).…”
Section: In Vivo Toxicity Of Chitosanmentioning
confidence: 98%
“…Gades and Stern reported that quantities exceeding 4.5 g chitosan taken daily by human volunteers did not result in toxic effects (Gades & Stern, 2003). In addition, human trials up to twelve weeks showed no toxic effects, no allergies, and only nausea symptoms and constipation in 2.6 -5.4% of subjects (Ylitalo et al, 2002).…”
Section: In Vivo Toxicity Of Chitosanmentioning
confidence: 98%
“…Since the shell of this animal contained significant amounts of chitin-chitosan biopolymer, it could be suggested that this reduction in blood pressure could reflect the ability of this compound to adsorb the lipids in the gut (Kanauchi et al 1994). Some studies have suggested there might be a reduction in blood pressure due to increased intake of chitosan, a positive high-density polymer that could attract and bind to the lipids (Ylitalo et al 2002;Gallaher et al 2002). In an acidic environment like the stomach, chitosan adsorbs fats during the digestion, facilitating their elimination through the feces.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, elevation of blood pressure in SHR was suppressed by the daily intake not only of FA, but also of CS-FA. On the other hand, CS-FA might change the CS-HCl salt in the stomach, allowing the salt to adsorb BA as well as CS-FA (Ylitalo, et al, 2002).…”
Section: Preparation Of Gel Beads Containing Cs-famentioning
confidence: 99%